Employee Engagement, Beban Kerja, dan Kepuasan Kerja terhadap Kinerja Karyawan: Studi di Kantor BPJS Kesehatan Cabang Tapaktuan - Salliyuana, Cut; Hidayat, Muhammad Rahmat; Damrus; Muzakir (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Human resources are an important asset in an organization. One way to retain employees in an organization requires increasing Employee Engagement, workload, and job satisfaction with employee performance. This research aims to identify key factors that influence employee performance from a subjective point of view and investigate how POB indicators and DCS aspects are reflected in employee experiences. This research design uses a qualitative method with a case study approach, research data is collected through in-depth interviews with employees so that conclusions can be obtained as a result of the research. The results of this research indicate that Employee Engagement has important value in improving employee performance. Employees who feel involved, have control in carrying out their work and feel valued by the organization tend to be more motivated and committed to making maximum contributions. On the other hand, excessive workload can have a negative impact on employee performance, causing stress, fatigue, and decreased productivity. However, if the workload is balanced with adequate control, optimal performance can be achieved. Job satisfaction plays an important role in improving employee performance. Employees who feel satisfied with their jobs tend to be creative, innovative and have a high level of commitment to the organization. The implication of this research is that it is important for organizations to develop strategies that enable employees to feel involved, overcome high workloads, and feel satisfied with their work so that they can improve the performance and services provided to JKN participants.